Educación Infantil y trabajo por proyectos Secuencias didácticas de literatura para las primeras edades - Mercadal, Neus Real; Correro, Cristina (FronteiraZ. Revista do Programa de Estudos Pós-Graduados em Literatura e Crítica Literária, 2016)
The model of didactic sequences (DS) in the shape of projects has an undeniable prestige in the field of literature didactics in the Spanish-Latin American ambit, but there are few studies on its applications in early childhood education. This article offers clues to design and implement literary projects in the classrooms of under seven year-old children and thus it provides teachers with practical tools for their literary education. To do so, we describe and contextualize the basic concepts and methodology of DS, their chances in early childhood education for literary education, and the axes to conceptualize and program literary projects. Two examples (developed in the framework of the initial training of the Early Childhood Education Degree at the Universidad Autónoma de Barcelona between 2013 and 2016) are finally included in order to clarify how to effectively carry out these projects.